Reinstatement of Crotalaria pellita (Leguminosae, Papilionoideae) and a new combination for its variety - Pandey, Arun Kumar; Subramaniam, Shweta (Phytotaxa, 2014)
This work is part of a study on the taxonomic revision of the genus Crotalaria in India. Based on the types and specimens examined, literature survey and the rules of ICN, we recognize Crotalaria pellita as the legitimate name and synonymize C. ramosissima. Further, a new combination for the variety C. ramosissima var. ramnadensis is hereby provided.